Synthesis and characterization of nebivolol: a review of different synthetic approaches and their efficiencies - Mim, Md. Rasel Mahmud (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.